Biodiversity and Aesthetics: some historical remarks (Itinera, 2025)
This article explores the historical roots of the aesthetic experience of biodiversity, focusing on a formative period of modern aesthetics between the mid-17th and late 18th centuries. Drawing on the works of Balthasar Gracián, Joseph Addison, and Johann Wolfgang von Goethe, the paper argues that the diversity and multitude of living species – what we now call biodiversity – were already central to proto-aesthetic and early aesthetic reflections on nature. Although lacking modern ecological awareness, these authors attributed profound emotional, philosophical, and symbolic value to the variety of life. Gracián’s concept of the innocent gaze, Addison’s aesthetic of novelty and fullness of being, and Goethe’s morphological insights into metamorphosis each exemplify a distinct mode of aesthetically engaging with biodiversity. The study concludes with critical reflections on the limits of linking aesthetic appreciation to ethical responsibility in contemporary debates on conservation, warning against instrumental or scientistic appropriations of aesthetic experience.
Keywords: Aesthetic experience of nature; Gracián; Addison; Goethe